2012
DOI: 10.1177/0885728811423653
|View full text |Cite
|
Sign up to set email alerts
|

Expanding Transition to Address the Needs of Students With Invisible Chronic Illness

Abstract: Many children with invisible chronic illnesses (ICIs) are living to adulthood, necessitating that they prepare for their future. Health care and education systems have different meanings and processes for transition, although both systems are designed to help young adults prepare for independence. As health care and educational services support and educate each child and the adult he or she will become, it makes sense for these systems to coordinate their services to improve student postschool outcomes. This a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…understanding diagnostically related symptoms, health management) of university-bound youth with disabilities are addressed (Cobb and Alwekk, 2009; Gil, 2007). Beyond collaboration, cross-disciplinary support coordination and research are needed to better understand and address the complicated and interrelated nature of academic and health transitions (Repetto et al, 2012; Repetto et al, 2013). …”
Section: Discussionmentioning
confidence: 99%
“…understanding diagnostically related symptoms, health management) of university-bound youth with disabilities are addressed (Cobb and Alwekk, 2009; Gil, 2007). Beyond collaboration, cross-disciplinary support coordination and research are needed to better understand and address the complicated and interrelated nature of academic and health transitions (Repetto et al, 2012; Repetto et al, 2013). …”
Section: Discussionmentioning
confidence: 99%
“…More recently, Morningstar et al (2010) found that the greater students perceived their families’ involvement in their transition process, and the more they received instruction on how to become involved in the IEP transition planning process, the greater students’ participation in the IEP transition planning process. The importance of self-determination instruction was again demonstrated with special populations, including girls (Coutinho, Oswald, & Best, 2006), culturally and linguistically diverse students and their families (Griffin, 2011; Valenzuela & Martin, 2005), and students with chronic health care needs (Repetto et al, 2012).…”
Section: Student Engagement In Transition Planningmentioning
confidence: 99%
“…The importance of self-determination instruction was again demonstrated with special populations, including girls (Coutinho, Oswald, & Best, 2006), culturally and linguistically diverse students and their families (Griffin, 2011;Valenzuela & Martin, 2005), and students with chronic health care needs (Repetto et al, 2012).…”
Section: Researchmentioning
confidence: 99%
“…Census Bureau, 2011), death rates for diseases (e.g., diabetes, cancer, heart disease, respiratory disease) declined by 10% to 28%. Because medical advances have increased survival rates, many students with special health care needs are attending public school, necessitating that they and their families prepare for their future (Gorter et al, 2011; Hamdani et al, 2011; Repetto et al, 2012).…”
Section: Health Concerns and Transition Iepsmentioning
confidence: 99%
“…Medical researchers have noted the need to coordinate with school systems to teach self-determination and self-advocacy skills needed by patients as they transition to adult medical facilities (Gorter, Stewart, & Woodbury-Smith, 2011; Hamdani et al, 2011). At the same time, researchers in education transition have advocated the expansion of education transition to include skills needed for HCT to improve postschool outcomes of students with health concerns (Repetto et al, 2012; Repetto, Gibson, Lubbers, Gritz, & Reiss, 2008). This merger would not only allow for teaching self-determination and self-advocacy skills but also support taking into account health concerns when planning for postschool outcomes.…”
mentioning
confidence: 99%